Plan de marketing para la ferretería Quezada Hermanos de la ciudad de Yanzatza, 2014 - Rodríguez Arévalo, José Eduardo (2015)
The overall objective of this research was to conduct a Strategic Marketing Plan for Hardware Quezada Brothers Yantzaza city, province of Zamora Chinchipe. Achieved by using inductive methods - deductive, which allowed them to validate the data obtained in the field study and then proceed to generalize to more general theoretical positions and contrast the general knowledge with those results and the use of research techniques as the survey and interview. We proceeded to conduct a situational analysis of the hardware Quezada Brothers, where an external analysis of the economic, social, technological and legal political factors was performed, proceeded to shape the analysis of Porter's five forces, the parent external factors structure - EFE yielding a weighted result of 3.29, showing that there are opportunities to be exploited to the maximum, just as the internal analysis where the company history is reviewed, its organizational structure, surveys applies to external clients running as inmates and their results are interpreted, allowing the array to build internal factors - EFI whose weighted result is 2.89, where it is found that the hardware has special capabilities that allow you to have a privileged position against competition. Finally, the conclusions that have been reached after the completion of this work, which is described as one of the most important are presented that: according to the results of the interview applied to the manager of the Hardware and contrasted with the result surveys aimed at internal customers of the company, it was determined what; Quezada Brothers Hardware Store does not have a marketing plan. Besides the recommendations environment arises at the end analysis presented you waiting to be taken into account by the directors of the company to improve its management, planning, organization and results